Le Pays basque : une région en quête d’identité - Severiano Rojo Hernández (Amnis)
This article discusses the nature of Basque identity and its influence on the conflict which affects the North of Spain. According to the author, the Basque issue does not come from an identitary conflict, but is produced by a deep disagreement between the different conceptions of Basque society. The conflict is difficult to resolve because political groups present completely opposite projects, using a discourse based on a very problematical argument: identity.